Desempenho fisiológico e bioquímico do meloeiro submetido à salinidade da água de irrigação - Silva, Fernando Henrique Alves da (2019)
Brazil is one of the main producers of fruits and vegetables in the world. The region of Brazilian Northeast stands out for the cultivation of melon (Cucumis melo L.), thanks to the favorable climatic conditions of this region. However, in recent years, due to the low rainfall, abiotic problems such as the increase in the EC of artesian wells have worried regional producers. Faced with this need and the lack of salinity-tolerant materials in the market, studies that allow the emergence of new materials that meet the producers and consumers are necessary. In experiment I, 24 accesses were used, with salinity of 0.06 and 3.45 dS m-1. Data were submitted to analysis of variance and means were compared by the Scott-Knott test (p<0.05) at the 5% probability level. The salinity affected the physiological quality of the melon seeds providing average germination of 62%, with average germination time of 4 days, average height of 10.5 cm and reduction in the accumulation of dry matter. The accesses that presented salinity intolerance were: A35, A24, A41, A31, A09, A28 and A43. The moderately tolerant accesses were: A16, A19, A15, A17, A34, A25, A27, A18 and A42. Salinity tolerants were: A45, A08, A37, A50, A14, A36, A07 and A39, which may serve as a basis for genetic improvement. In experiment II the effect of salinity (0.5 and 4.5 ds m-1) on eight melon accesses (A07, A14, A17, A24, A34, A35, A36, A39) and two commercial hybrids: Sancho and Caribbean Gold were evaluated, making a total of 10 materials. The experimental design was a randomized block design with eight repetitions. The treatments were arranged in a 2 x 10 factorial scheme (salinity levels x materials). Stress reduced stomatal conductance (gs) and consequently decreased transpiration rate (E) and liquid photosynthesis (A). The efficiency of the intrinsic water use (A/gs) increased in some accesses. The K/Na+ ratio was higher in the leaves, smoothing the ionic stress caused by Na+ and Cl-. The A24 access was classified as susceptible to salinity, with low production efficiency. The A35 access stood out with high performance in gas exchange and growth analysis, evidenced by the analysis of main components as a different material from the others, and did not present great differences regarding the increase in EC of irrigation water shown in the analysis of main components, indicating this as salinity tolerant. In experiment III the objective was to evaluate the behavior of melon materials in the physiology and biochemistry of plants and fruits according to the EC doses of irrigation water. The experimental design was randomized blocks in a factorial scheme (5 x 3) with 5 repetitions totaling 75 plots, performing a regression analysis for all variables analyzed. The first factor was represented by treatments with five salinity levels (T1 = 0.5, T2 = 1.5, T3 = 3.0, T4 = 4.5 and T5 = 6.0 dS m-1) and the second factor by the A35 and A24 accesses and the Sancho hybrid. Biochemical markers RWC, total carbohydrate and extravasation evidenced the better A35 and Sancho in osmoregulation. H2O2 and MDA were reduced for A35 access and Sancho with increased SOD and APX activity for these materials, indicating them as salinity tolerant. Production was reduced, with smaller fruits (length and width), of lower weight. Vitamin C and yellow flavonoids increased, indicating antioxidant power against ROS. Materials showed similar post-harvest behavior, but Sancho stood out from the rest, possibly because it was an improved material. The A24 access showed physiological and biochemical responses that classify it as intolerant